2010
DOI: 10.1002/jmri.22251
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion MRI in neuro‐psychiatric systemic lupus erthemathosus

Abstract: Purpose: To use perfusion weighted MR to quantify any perfusion abnormalities and to determine their contribution to neuropsychiatric (NP) involvement in systemic lupus erythematosus (SLE). Materials and methods:We applied dynamic susceptibility contrast (DSC) perfusion MRI in 15 active NPSLE, 26 inactive NPSLE patients, and 11 control subjects. Cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT) maps were reconstructed and regions of interest were compared between groups. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(39 reference statements)
4
22
2
Order By: Relevance
“…[16][17][18] These studies were performed using different MR scanners and were conducted on different subject groups including SLE patients with depression and visible brain lesions, which may explain the discrepancy between their and our results. Our results are in accordance with the study by Emmer et al 15 performed with a 1.5 Tesla scanner. Similarly to that study we also did not find any significant hypoperfusion, within either gray or white matter of patients with NPSLE and SLE, though we noticed a tendency to lower values of rCBV in several cortical regions in both patient subgroups.…”
Section: Discussionsupporting
confidence: 96%
“…[16][17][18] These studies were performed using different MR scanners and were conducted on different subject groups including SLE patients with depression and visible brain lesions, which may explain the discrepancy between their and our results. Our results are in accordance with the study by Emmer et al 15 performed with a 1.5 Tesla scanner. Similarly to that study we also did not find any significant hypoperfusion, within either gray or white matter of patients with NPSLE and SLE, though we noticed a tendency to lower values of rCBV in several cortical regions in both patient subgroups.…”
Section: Discussionsupporting
confidence: 96%
“…Our findings are in agreement with a similar study by Emmer et. al., which looked at larger areas of subcortical grey matter and central white matter and thalamus using larger ROI’s than in the present study and also did not find any statistically significant MR perfusion abnormalities in NPSLE patients compared to SLE and HC patients 9 .…”
Section: Discussioncontrasting
confidence: 58%
“…This significantly increased variability in CBF and CBV seen in NPSLE patients might partially explain why no significant changes in perfusion measures in NPSLE patients have been seen in previous studies and why researchers are struggling to find a specific diagnostic target for NPSLE 9,15,16 . Perhaps multiple concordant targets are necessary, or alternatively the diagnosis of NPSLE is too broad, and if narrowed, might render a clearer diagnostic tool.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They have also demonstrated that the relative reduction in NAA in SLE patients might be transient, and it is probably dependent on disease activity, as NAA will increase after treatment and will change in patients going from having active to inactive disease (15,36). The role that disease activity might have on cerebral metabolic activity is supported by previous studies that have demonstrated changes in cerebral vascularity in SLE patients with active disease with elevated cerebral blood flow, cerebral blood volume, and mean transit time compared to HC subjects (3739). Interestingly, despite a correlation between SLEDAI and the NAA at baseline, there were no correlation between the SLEDAI score improvement and the increase in NAA/Cr over time.…”
Section: Discussionmentioning
confidence: 71%